Thermal behavior of NBR vulcanizates activated with plant-extract-derived magnesium oxide - Arianne Aparecida da Silva; Ana Maria Furtado de Sousa; Cristina Russi Guimarães Furtado; Nakédia M. F. Carvalho (Polímeros)
Abstract This study compares the thermal degradation and aging resistance of NBR compounds activated with ZnO or MgO-green synthesized with the assistance of Camellia sinensis extract. Thermal degradation was studied using the Flynn-Wall-Ozawa method. Aging resistance was investigated by the changes in crosslink density and mechanical properties before and after the samples are exposed in a forced-air oven at 100 °C/72 h. The activation energies for NBR compounds with MgO-green and ZnO are, respectively, 220 kJ mol-1 and 700–200 kJ mol-1. After oxidative-thermal aging, the crosslink density of NBR compounds goes up by 24% with MgO-green and 120% with ZnO. Consequently, the changes in hardness and tensile properties of the NBR with MgO-green are more subtle than those observed with ZnO. Based on Fisher's minimum significant difference procedure, the data analysis shows that MgO-green can be used instead of ZnO as an activator in the vulcanization of NBR.